Synthesis, Characterization and Biological Activity of Ni(II), Cu(II) and Fe(III) Complexes Derived from N2,N6-bis(5-Mercapto-1,3,4-thiadiazol-2-yl)pyridine-2,6-dicarboxamide - Kumar, Anuroop; Pal Singh, Netra; Agrawal, Uma; Kumar, Kaushal (Asian Journal of Chemistry, 2020)
Novel metal complexes of the type [M(L)X] (where M= Cu(II), Ni(II) and Fe(III), L = N2,N6-bis(5-mercapto-1,3,4-thiadiazol-2-yl)pyridine-2,6-dicarboxamide, X= Cl−, CH3COO−) were synthesized by the reaction of pyridine-2,6-dicarboxylic acid and 2-amino-5-mercepto-1,3,4-thiadiazole. The synthesized ligand was reacted in THF with metal salts (Cu, Ni and Fe) to form complexes. Deprotonated ligand shows tridentate nature and coordinate to metal ion to form pincer cavity. In all, complexes metals were surrounded by three nitrogen atom and other site coordinated by other groups (chloride, acetate). All the synthesized complexes were characterized by spectroscopic techniques like UV-visible, 13C NMR and 1H NMR, IR spectroscopy, DSC, elemental analysis and molar conductance measurements. The ligand and its metal complexes were tested for antimicrobial activity against bacterial and fungal strains by determining inhibition zone, minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). The complexes showed moderate antimicrobial activity and antifungal activity when tested against bacteria and fungi.